Gradient crystallinity and its influence on the poly(vinylidene fluoride)/poly(methyl methacrylate) membrane‐derived by immersion precipitation method. Issue 27 (9th November 2019) - Remanan, Sanjay; Ghosh, Sabyasachi; Das, Tushar Kanti; Sharma, Maya; Bose, Madhuparna; Bose, Suryasarathi; Das, Amit Kumar; Das, Narayan Chandra
ABSTRACT: Herein, phase inversion poly(vinylidene fluoride)/poly(methyl methacrylate) (PVDF/PMMA) microporous membranes were prepared at various PMMA concentration by immersion precipitation method. Increment in the PMMA concentration has a significant influence in the PVDF membrane crystallinity, which is studied by differential scanning calorimeter, X‐ray diffractometer, and small‐angle X‐ray scattering analyses. Properties such as membrane bulk structure, porosity, hydrophilicity, mechanical stability, and water flux vary in terms of PMMA concentration. Porosity is increased, and tensile strength decreased when PMMA concentration is beyond 30 wt %. Thermodynamic instability during the liquid to solid phase separation and variation in the crystallinity has an intense effect on these membrane properties. Then, 70/30 blend membrane selected as optimum composition owing to the high porosity and pure water flux compared to other compositions. This membrane is modified with a composite filler derived from the graphene oxide and titanate crosslinked by chitosan. The antibacterial, antifouling, and bovine serum albumin separation studies reveal that the developed nanocomposite membrane is a potential candidate for the separation application. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48677. Abstract : Variation in PVDF membrane crystallinity in the presence of PMMA polymer.